Leveraging Portfolio Websites as Business Process Management Enablers to Improve Operational Effectiveness: A Case Study of a Technology Service Company - Abdul Malik; Muhammad Eka; Razvan Serban (Ali Institute of Reseach and Publication, 2026)
Business Process Management (BPM) is a systematic approach to optimize business processes through continuous improvement cycles. This research aims to analyze the implementation of BPM in improving operational effectiveness at PT. Aguna Poda Natoras through the development of a company portfolio website. Using qualitative research methods through in-depth interviews, observations, and document analysis, this study found that the implementation of BPM through portfolio website development provides significant impact on process efficiency, service quality improvement, and better coordination between departments. This research contributes a novel framework demonstrating how portfolio websites can serve as operational enablers in BPM implementation, specifically in technology service companies, bridging the gap between digital transformation strategy and measurable business outcomes through quantifiable improvements in lead conversion (75%), sales cycle reduction (50%), and response time enhancement (80%). The portfolio website serves as a digital platform that supports marketing processes, client communication, and company branding. Success factors include management commitment, employee involvement, appropriate technology selection, and continuous improvement culture. This research provides practical contributions for companies in designing effective BPM implementation strategies through digital transformation.